2022
DOI: 10.3390/ijms23179654
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Glycogen Synthase Kinase 3 Significantly Inhibits Chitin and Fatty Acid Metabolism in Asian Citrus Psyllid, Diaphorina citri

Abstract: Glycogen is a predominant carbohydrate reserve in various organisms, which provides energy for different life activities. Glycogen synthase kinase 3 (GSK3) is a central player that catalyzes glucose and converts it into glycogen. In this study, a GSK3 gene was identified from the D. citri genome database and named DcGSK3. A reverse transcription quantitative PCR (RT-qPCR) analysis showed that DcGSK3 was expressed at a high level in the head and egg. The silencing of DcGSK3 by RNA interference (RNAi) led to a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Glucose and fatty acid metabolism plays a crucial role in energy metabolism, which provides the energy required for life processes, such as growth and development. 38 However, great rates of glycogen and fatty acids synthesis are exhibited in obesity and plasma free fatty acids might cause the hepatic glycogen content that is associated with obesity and insulin resistance. 39 Similar with the study of high-fat diet fed mice, 40 we observed that the serum lipids levels were significantly decreased in TRE-DG and the expressions of genes involved in the bioenergetic pathway were reversed in DG after TRE intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose and fatty acid metabolism plays a crucial role in energy metabolism, which provides the energy required for life processes, such as growth and development. 38 However, great rates of glycogen and fatty acids synthesis are exhibited in obesity and plasma free fatty acids might cause the hepatic glycogen content that is associated with obesity and insulin resistance. 39 Similar with the study of high-fat diet fed mice, 40 we observed that the serum lipids levels were significantly decreased in TRE-DG and the expressions of genes involved in the bioenergetic pathway were reversed in DG after TRE intervention.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous protocol, the dsRNA was delivered by microinjection (Zhang et al, 2022). In brief, 180 fifth‐instar D. citri nymphs were divided into nine groups, three of which were treated with ds DcCDA2a , three with ds DcCDA2b , and the remaining three groups were treated with ds GFP .…”
Section: Methodsmentioning
confidence: 99%
“…The next three studies presented in this Special Issue are dedicated to the impact of GSK3 modulation on central cellular processes, i.e., cell cycle progression [23], the management of amino acid (aa) deprivation [24], and metabolism [25]. Shenker et al, for instance, were interested in elucidating the cytotoxic properties of Aggregatibacter actinomycetemcomitans-derived cytolethal distending toxin (AaCdt) [23], a heterotrimeric bacterial toxin possessing both DNase and lipid phosphatase activity, which typically causes cell cycle arrest and apoptosis [26].…”
mentioning
confidence: 99%
“…In the next study, metabolic regulation was revisited as one of the most prominent functions of GSK3. Zhang et al identified a GSK3 homolog (termed DcGSK3) closely related to GSK3 genes of the Hemptera species in Diaphorina citri Kuwayama (also known as Asian Citrus Psyllid) [25], a hemipteran bug acting as a vector for Candidatus Liberibacter asiaticus, the bacterium causing citrus greening disease [30]. DcGSK3 expression could be demonstrated among all tissues and developmental stages analyzed, with the highest levels in the head and during the egg phase, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation